2018
DOI: 10.1155/2018/9478630
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Species in the Modulation of Gut Microbiota: An Overview

Abstract: Probiotics are microbial strains that are beneficial to health, and their potential has recently led to a significant increase in research interest in their use to modulate the gut microbiota. The animal gut is a complex ecosystem of host cells, microbiota, and available nutrients, and the microbiota prevents several degenerative diseases in humans and animals via immunomodulation. The gut microbiota and its influence on human nutrition, metabolism, physiology, and immunity are addressed, and several probiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
400
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 605 publications
(458 citation statements)
references
References 78 publications
9
400
0
13
Order By: Relevance
“…Previously we have shown that polyphenol‐rich GSF significantly reduced HF‐induced intestinal permeability and hepatic inflammation. Probiotics such as lactobacillus have known to modulate intestinal permeability . The current study showed a reduction of genes ( Nr1d1, Raet1b, Spon2 ) associated with response to LPS and immune response following GSF and LAB supplementation.…”
Section: Discussionsupporting
confidence: 53%
“…Previously we have shown that polyphenol‐rich GSF significantly reduced HF‐induced intestinal permeability and hepatic inflammation. Probiotics such as lactobacillus have known to modulate intestinal permeability . The current study showed a reduction of genes ( Nr1d1, Raet1b, Spon2 ) associated with response to LPS and immune response following GSF and LAB supplementation.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, a higher abundance of Ruminococcaceae was detected in obese than normal weight mice (Kim et al ). Bifidobacteria has been shown to be involved in nutrient metabolism and energy recycling, which play important roles in the trophic, metabolic and protective functions of the host (Blais et al ; Azad et al ). Our study showed that the abundance of Oscillibacter decreased in the jejunum of IUGR piglets at 21 days of age, as well as Bifidobacterium in the ileum of IUGR piglets at 28 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from animals and humans have indicated that there is a marked difference in the gut microbiota between obese and lean subjects, and the microbiota in the obese may further manipulate host metabolism leading to enhanced adiposity, inflammatory response, oxidative stress, and metabolic dysfunction . Xu et al also indicated that melatonin improves the richness and diversity of gut microbiota and reverses 14 operational taxonomic units (OTUs) in HF diet‐fed mice, especially for the ratio of Firmicutes to Bacteroidetes .…”
Section: Introductionmentioning
confidence: 99%